Study of Demographic Determinants, Clinical Spectrum and Surgical Management of Diabetic Foot Ulceration: a Cross-Sectional Analysis - Dr. Gaurav Patil; Dr. Sonali Gaurav patil; Dr. Pranjali Sanjay Patil; Dr. Vaibhav Sanjay Deshmukh (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Introduction: Diabetic foot ulceration (DFU) is a major complication of diabetes mellitus, contributing significantly to morbidity, infection risk, and lower limb amputations. Understanding its demographic determinants and clinical spectrum is essential for timely intervention and improved outcomes. Aim: To evaluate the demographic risk factors, clinical characteristics, and surgical management modalities associated with DFU in patients attending a tertiary care teaching hospital in India. Methods: A prospective, cross-sectional observational study was conducted from 2024 to 2025, involving 130 patients with type 2 diabetes mellitus—65 with DFU and 65 matched controls without DFU. Data on age, gender, diabetes duration, HbA1c levels, smoking history, ulcer type, duration, infection status, and management strategies were collected. Wagner grading was used to assess ulcer severity. Statistical analysis included chi-square testing for categorical associations. Results: DFU was significantly associated with age ≥60 years (64.6%), male gender (70.8%), diabetes duration >10 years (60%), poor glycemic control (HbA1c >8% in 72.3%), and smoking history (40%). Neuropathic ulcers were most common (43.1%), with 50.8% persisting for 4–12 weeks. Infection was present in 47.7% and osteomyelitis in 27.7%. Management included glycemic optimization (93.8%), antibiotics (80%), surgical debridement (41.5%), and minor amputations (29.2%). No significant association was found between Wagner grade and infection status (p = 0.81). Conclusion: DFU is strongly linked to advanced age, male gender, long-standing diabetes, poor glycemic control, and smoking. Multimodal management including early surgical intervention and metabolic optimization is essential. Wagner grading alone may not reliably predict infection risk, underscoring the need for comprehensive clinical assessment.